1996
DOI: 10.1002/bjs.1800830836
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of D2 lymph node dissection for patients with gastric cancer and pN0 and pN1 lymph node metastases

Abstract: A retrospective immunohistological analysis of 100 patients with pT1-3 N0 and pT1-3 N1 gastric adenocarcinoma demonstrated a high frequency of micro-involvement in the removed lymph nodes. The presence of three or more tumour cells in more than 10 per cent of the lymph nodes was of significant prognostic value in the pN0 cases. Multivariate analysis identified micro-involvement as an independent prognostic factor. The results explain why patients benefit from lymphadenectomy even if the removed lymph nodes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
116
3
18

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(143 citation statements)
references
References 15 publications
6
116
3
18
Order By: Relevance
“…Therefore, radical lymphadenectomy for gastric cancer has become a standard procedure, resulting in the long-term survival of patients with lymph node metastasis (Maehara et al, 1992). Nevertheless, several authors have reported that complete resection with radical lymphadenectomy that led to a nodenegative (pN0) final diagnosis according to routine histological haematoxylin -eosin (HE) staining did not prevent recurrence (Maehara et al, 1996;Siewert et al, 1996;Ishida et al, 1997). The key causative factor of recurrent gastric cancer is lymph node micrometastasis.…”
mentioning
confidence: 99%
“…Therefore, radical lymphadenectomy for gastric cancer has become a standard procedure, resulting in the long-term survival of patients with lymph node metastasis (Maehara et al, 1992). Nevertheless, several authors have reported that complete resection with radical lymphadenectomy that led to a nodenegative (pN0) final diagnosis according to routine histological haematoxylin -eosin (HE) staining did not prevent recurrence (Maehara et al, 1996;Siewert et al, 1996;Ishida et al, 1997). The key causative factor of recurrent gastric cancer is lymph node micrometastasis.…”
mentioning
confidence: 99%
“…Furthermore, gastrectomy with D2 lymphadenectomy can be performed with a low complication rate and was found to significantly improve the 5-year survival rate. Siewert et al (1996) claimed that D2 lymphadenectomy could improve prognosis in patients without lymph node metastases. The reason for this improvement is that the micrometastases found in approximately 10% of the cases can only be detected with immunohistochemical techniques that are not routinely used.…”
Section: Discussionmentioning
confidence: 99%
“…There are others definitions for micrometastasis as malignant cells cluster smaller than 2 mm in diameter 32 , smaller than 0.5 mm 27 and 5 or less cells 15 , all of them with stromal reaction such as granulation or desmoplastic tissue. In the other hand microinvolvement can be described as individual tumor cells without stromal reaction 32 .…”
Section: Discussionmentioning
confidence: 99%